2020
DOI: 10.1007/978-3-030-50516-5_18
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Prediction of Lung Cancer Survival Rates Using 2D Features from 3D Scans

Abstract: The survival rate of cancer patients depends on the type of cancer, the treatments that the patient has undergone, and the severity of the cancer when the treatment was initiated. In this study, we consider adenocarcinoma, a type of lung cancer detected in chest Computed Tomography (CT) scans on the entire lung, and images that are "sliced" versions of the scans as one progresses along the thoracic region. Typically, one extracts 2D features from the "sliced" images to achieve various types of classification. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…-Although a lot of work has been done when it concerns the diagnosis of lung cancer, the work related to the survival times and their correlation to the size/shape of the tumor is relatively unexplored. In an earlier paper [10], we had shown that by a regression analysis, we can predict the survival times based on various features of the tumor. This paper builds on those results to use ensemble machines and block-diagonal phenomena.…”
Section: Contributions Of This Papermentioning
confidence: 99%
See 4 more Smart Citations
“…-Although a lot of work has been done when it concerns the diagnosis of lung cancer, the work related to the survival times and their correlation to the size/shape of the tumor is relatively unexplored. In an earlier paper [10], we had shown that by a regression analysis, we can predict the survival times based on various features of the tumor. This paper builds on those results to use ensemble machines and block-diagonal phenomena.…”
Section: Contributions Of This Papermentioning
confidence: 99%
“…In our application domain [9], [10], the dimensionality of the feature vector is 110. Computing the eigenvalues and eigenvectors of such a large matrix is, certainly, time consuming.…”
Section: Invoking Block Diagonalization and Ensemble Regressionmentioning
confidence: 99%
See 3 more Smart Citations